Expression of tenascin-C in aseptic loosening of total hip replacement - Konttinen, Y. (1998)
OBJECTIVE—To assess if the bonding interlayer between the implant and bone in aseptic loosening of total hip replacement (THR) is qualitatively deteriorated by excessive accumulation of anti-adhesive glycoprotein, tenascin-C. METHODS—Alkaline phosphatase-anti-alkaline phosphatase (APAAP) method was used for immunohistochemical staining of tenascin-C in interface tissue and control synovial tissue. RESULTS—Tenascin-C was found to be a major component of the extracellular matrix at a hitherto unrecognised site, namely the synovial membrane-like interface tissue between implant and bone in aseptic loosening of THR. The overall tenascin-C staining (median score 4.0) was greatly increased in aseptic loosening compared with synovial membrane (median score 2.0; p<0.001) and fibrous capsule (median score 2.0; p<0.001) from primary THR operations. Topological analysis disclosed that tenascin-C was also found at the critical implant-interface and interface-bone surfaces. CONCLUSION—Local tenascin-C expression is increased as a result of a chronic foreign body type reaction associated with excessive cytokine production and tissue injury mediated by microtrauma and neutral endoproteinases. This qualitative and topological deterioration of the bonding interlayer by an increase of anti-adhesive tenascin-C expression may inadvertantly contribute to loosening.   Keywords: tenascin; aseptic loosening; total hip replacement